The Development of Android-Based Islamic Education Learning Media - Ahmad Maulani; Sovia Mas Ayu; Oki Dermawan; Muhammad Akmansyah (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2021)
The purpose of this study was to develop instructional media, describe the feasibility of learning media, describe the response of android media users, and describe the effectiveness of Android-based learning media on Islamic Education subjects. The type of the research was R & D with the ADDIE development model. This study took the subject of educators and 10th graders at Darussalam Sumberejo Vocational School Tanggamus Lampung. Data collection used questionnaires and interviews. The results showed that the Android-based Islamic education learning media named Islamuna was suitable for general use and was effective in improving student learning outcomes. The increase in student learning outcomes can be seen in the pretest and posttest scores with an average of 68.5 and 81.33.